Analysis of ceiling type to produce energy efficient residential buildings: case study on housing design of puskim pu-bandung city - Nurina Vidya Ayuningtyas; Istiana Adianti; Jatmika Adi Suryabrata (Universitas Gadjah Mada, 2021)
Many houses that exist on this earth. Therefore, it is necessary to have tactical and intelligent thinking in designing a home. Many things are rarely considered related to the effects of the design of building elements when related to the temperature or the energy produced. Existing background regarding efforts to reach a comfortable temperature can not only be solved in terms of mechanical systems, but the architectural approach can help and provide a comfortable effect for its inhabitants. This research was conducted to determine the level of thermal comfort or temperature in the room of a residential design that would be related to the size of energy consumption by applying several alternative designs or ceiling forms. This type of research is research using simulation methods through a computer model. The results showed the use of ceiling type Vaulted Ceiling was able to increase the Surface Inside Temperature value by 3 ° C when compared to the type of drop ceiling. The Mean Radiant Temperature value when using the ceiling vault type rises 0.6 ° C and on the acquisition of Operative, Temperature rises 0.3 ° C. The use of insulation material on the roof can significantly reduce Mean Radiant Temperature and Operative Temperature at 1.7 ° C at Mean Radiant Temperature and 0.8 ° C at Operative Temperature. Seeing the results of the simulation in this study, the recommended ceiling type is to use the drop ceiling type because it is quite capable of keeping the temperature in the room not too high so that thermal comfort can be achieved. However, if you want to apply a ceiling design with a model or type of drop ceiling, it is better to use additional insulation material so that the heat transmission temperature is not too high in the room.